2016
DOI: 10.3762/bjoc.12.232
|View full text |Cite
|
Sign up to set email alerts
|

Methylenelactide: vinyl polymerization and spatial reactivity effects

Abstract: The first detailed study on free-radical polymerization, copolymerization and controlled radical polymerization of the cyclic push–pull-type monomer methylenelactide in comparison to the non-cyclic monomer α-acetoxyacrylate is described. The experimental results revealed that methylenelactide undergoes a self-initiated polymerization. The copolymerization parameters of methylenelactide and styrene as well as methyl methacrylate were determined. To predict the copolymerization behavior with other classes of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Later, the same authors published a complementary study on the kinetics of free‐radical and RAFT‐mediated MLA polymerization, as well as its copolymerization with styrene, MMA, and N , N ‐dimethylacrylamide. [ 447 ] The reactivity of MLA was found to be similar to that of MMA. However, it was observed that MLA could self‐initiate its polymerization in AIBN‐free experiments.…”
Section: Polymerization Of (Meth)acrylic Monomers and Analogsmentioning
confidence: 99%
“…Later, the same authors published a complementary study on the kinetics of free‐radical and RAFT‐mediated MLA polymerization, as well as its copolymerization with styrene, MMA, and N , N ‐dimethylacrylamide. [ 447 ] The reactivity of MLA was found to be similar to that of MMA. However, it was observed that MLA could self‐initiate its polymerization in AIBN‐free experiments.…”
Section: Polymerization Of (Meth)acrylic Monomers and Analogsmentioning
confidence: 99%
“…57). A detailed mechanism of radical polymerization of exo-methylene lactide is described by Britner and Ritter [307], which explains the formation of isotactic, syndiotactic, and atactic poly-exo-methylene lactides (Fig. 58).…”
Section: Halogenation and Other Reactionsmentioning
confidence: 99%
“…Recently, Britner and Ritter [ 58 , 59 ] reinvestigated Scheibelhoffer’s first study of a radical polymerizable lactide derivative with respect to polymerization and polymer analogous aminolysis under mild conditions. In this work, the optically active MLA was polymerized by free radical polymerization in solution using AIBN as an initiator and resulted in isotactic-biased atactic optically active poly(methylenelactide) (PMLA) with molecular weights ranging between 4 × 10 4 –1 × 10 5 g mol −1 with dispersity, Đ ~2.5 and a T g of 244 °C.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous works, PMLA has poor solubility, sluggish dissolution, and that it is challenging to handle the polymer as a melt for polymerization. As previously mentioned, Britner et al [ 58 , 59 ] have found a way to overcome this challenge by PMLA functionalization. In the underlying study, Britner and Ritter focused on spatial effects with respect to interactions between neighboring lactide rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation